Discovery of Rogaratinib (BAY 1163877): a pan‐FGFR Inhibitor. (16th February 2018) - Collin, Marie‐Pierre; Lobell, Mario; Hübsch, Walter; Brohm, Dirk; Schirok, Hartmut; Jautelat, Rolf; Lustig, Klemens; Bömer, Ulf; Vöhringer, Verena; Héroult, Mélanie; Grünewald, Sylvia; Hess‐Stumpp, Holger
Abstract: Rogaratinib (BAY 1163877) is a highly potent and selective small‐molecule pan‐fibroblast growth factor receptor (FGFR) inhibitor (FGFR1–4) for oral application currently being investigated in phase 1 clinical trials for the treatment of cancer. In this publication, we report its discovery by de novo structure‐based design and medicinal chemistry optimization together with its pharmacokinetic profile. Abstract : In phase 1 : We disclose the discovery and chemical structure of rogaratinib (BAY 1163877), a highly potent and selective pan‐FGFR inhibitor currently being assessed in clinical trials for the treatment of cancer. We describe the structure–activity relationship and the pharmacokinetic profile of the benzothiophenyl‐pyrrolotriazine structure class.